Effect of Predator Fear on the Dynamics of a Delayed Hassell-Varley Model with Nonlinear Prey Harvesting Effort using Imprecise Biological Parameters - Bhattacharya, Aditya; Bhattacharyya, Anindita (Journal of Applied Nonlinear Dynamics, 2026)
In this paper, we studied the dynamical behaviour of Hassell-Varley model in the presence of non-linear harvesting and Richards’ growth in prey population by using imprecise biological parameters. Moreover, anti-predator behaviour and discrete time delay due to gestation or digestion of the species are considered in the model system. The positivity and boundedness of the system are studied and the criterion for the extinction of the predator-prey populations are discussed. The criterion for the co-existence of prey and predator, and their stability is studied analytically. In addition, the effect of fear factor on the dynamics of the system is studied. Moreover sufficient condition for the hopf bifurcation was noted under consideration of discrete time delay and for other different biological parameters. Numerical simulations are presented to validate the analytical results obtained and with the outcome the biological relevance of the model is discussed.